A critical investigation of dangerous goods procedures in logistics operations. - Wojtczuk, Kamil (2012)
University of Nottingham “A critical investigation of dangerous goods procedures in logistics operations.” Kamil Wojtczuk MSc Logistics and Supply Chain Management